A total systems analysis on the Old Swiss Inn - Caram, Sofia Laureen A.; Lazatin, Sebastian Luis Y.; Marañon, Miguel Paolo T.; Vergara, Samantha Kaye C.; Tamayao, Mili-Ann (Quezon City College of Engineering, University of the Philippines Diliman, 2019)
Old Swiss Inn is an establishment from the 1940s which has grown to two restaurants and has expanded their services to include a catering arm, a bakeshop, and a commissary. It is one of the few restaurants in Metro Manila that serves authentic Swiss dishes in an environment that encapsulates the feeling of dining in a quaint restaurant in the Swiss Alps. Moreover, the Old Swiss Inn is recognized for its culinary excellence. Hence, there is a premium on strict adherence to uncompromising standards and consistency. It was identified that over the last quarter of 2018, Old Swiss Inn encountered spoilage costs amounting to Php 114,077.50. Over the same time period, the company had also incurred additional operational costs amounting to Php 11,250.00 from the hours spent manually managing inventory. The aforementioned factors result to an estimate of Php 501,310.36 contribution to the annual total costs of the company. Cost inefficiencies can be attributed to three main pain points: (1) no system for inventory management, (2) non-optimized ordering process, and (3) no standardization -- no standard order schedule and quantities. In order to address these issues, the proposed solution is to make all processess Accessible, Custom, and Timely (A.C.T.) Three main solutions were implemented. First, the stock requisition slips were transferred to google sheets which reduced the process time by 32.40% and printing costs by 100%. Second, bar scanning for inventory management was implemented and showed a time reduction of 49.28% compared to manually managing inventory. The Php 20,808.41 computed amount of savings from improving process efficiency are linked to the wages and time consumed in the process of filling up and accomplishing SRS forms and conducting month end inventory checks in the stockroom. Lastly, a dynamic inventory module that automatically determines the optimal inventory levels for any ingredient was implemented for the most frequently ordered ingredients. The most frequently ordered ingredients are mostly perishable and contribute to the spoilage costs experienced by the company. By implementing this module, the spoilage costs are lowered by Php 319,417.25 per annum. Overall, the new system aims to lower the additional Php 501,310.36 annual cost incurred by the company from spoilage and inefficiencies by Php 358,401.16 or 71.5% of the initial value.
Feasibility study.
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design.
Keywords: Old Swiss Inn; Restaurants -- Philippines; System analysis